2020
DOI: 10.1007/s00167-020-06355-0
|View full text |Cite
|
Sign up to set email alerts
|

No difference in 13-year survival after medial pivot or central pivot mobile bearing total knee arthroplasty. A propensity matched comparative analysis

Abstract: Purpose The present study was designed to evaluate the long-term results (more than 10 years) of mobile bearing total knee arthroplasty (TKA) and to compare the survival of medial pivot axis (MPA) and central pivot axis (CPA) TKAs. The primary hypothesis was that the 10-to 15-year survival rate of MPA TKAs will be better than CPA TKAs. Methods A national, multicenter, retrospective study was performed in France. In this case-control design, 1154 TKAs were paired into the CPA group (control group: 577 cases) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“… 44 Another article found no difference in survivorship at 13 years between MP and central mobile-bearing TKAs. 45 In a recent review article, Cacciola et al 46 found that primary MP implants in general provide overall mid-term survivorship comparable to standard cruciate-retaining and posterior-stabilized implants, according to the available data, and yield better high-end function than standard implants.…”
Section: Discussionmentioning
confidence: 99%
“… 44 Another article found no difference in survivorship at 13 years between MP and central mobile-bearing TKAs. 45 In a recent review article, Cacciola et al 46 found that primary MP implants in general provide overall mid-term survivorship comparable to standard cruciate-retaining and posterior-stabilized implants, according to the available data, and yield better high-end function than standard implants.…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the nine studies included reported no reoperations or revisions due to aseptic loosening [21,22,[24][25][26][27]29]. Only two studies highlighted instances of revisions because of aseptic loosening, marking a prevalence rate of 0.4% [23,28]. Karachalios et al [23] and Jenny et al [28] registered a revision prevalence due to aseptic loosening of 1.2%, corresponding to 3 out of 251 and 4 out of 335 MP-TKAs, respectively.…”
Section: Causes Of Reoperationsmentioning
confidence: 99%
“…Initially, 667 records were identified through the database search. After removing duplicates and applying the inclusion and exclusion criteria, nine studies were ultimately selected for qualitative analysis [21][22][23][24][25][26][27][28][29] (Figure 1). resolution was sought via consultation with the senior author (GS).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations